USING OF ONLINE MATHEMATICS LEARNING MEDIA IN CLASS VIII SMP NEGERI 1 PASIR PENYU - Khairun Nisa; Desti Handayani (Jurnal Prinsip Pendidikan Matematika, 2022)
The COVID-19 pandemic has significantly impacted various sectors, such as health, social, political, economic, and education. Educators must ensure that teaching and learning activities continue, even though students are home. The Central and Regional Governments took the Large-Scale Social Restriction Policy (PSBB) to contain the spread of the Corona-19 virus, which has disrupted the face-to-face learning process. The solution, educators design learning media as innovations by utilizing bold media (online). This is in accordance with the Minister of Education and Culture of the Republic of Indonesia regarding Circular Letter Number 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of Corona Virus Disease (COVID-19). Educators can do learning together simultaneously using groups on social media such as WhatsApp (WA), telegram, Instagram, zoom application, google meet, learning videos via youtube links, and other media as learning media. The method used in writing this article is a qualitative method that describes something based on data and numbers narrated in concluding sentences. Besides that, the writing of this article is library research.